Nomograms of fetal cardiothoracic ratio from 17 to 37 weeks' gestation as assessed by three different measurement techniques and their correlation with gestational age - Nalat Sompagdee (2022)
Objective: To create nomograms for fetal cardiothoracic (CT) ratio as assessed by three different 2-dimensional sonographic measurements, including CT diameter, circumference, and area ratios, in Thai fetuses with a gestational age (GA) of 17–37 weeks, and to evaluate both their correlation with GA or biparietal diameter (BPD) and variability among the three measurement methods. Methods: Two-dimensional sonographic measurements of fetal CT ratio in 4-chamber view were assessed by three different measurement techniques. The 95% reference intervals and Z-scores of all measurement methods based on GA or BPD were constructed. Intraclass correlation coefficients (ICC) for the reproducibility of each technique were compared. Results: A total of 511 uncomplicated singleton pregnancies were included. The fetal CT ratio values by all measurement techniques gradually and smoothly increased with increasing GA and BPD. The fetal CT circumference ratio showed the least correlation with both GA and BPD. The intraobserver and interobserver reliability coefficients of all techniques demonstrated almost excellent agreement (all ICCs at least 0.87). Conclusion: Reference intervals and Z-score reference ranges were developed using three different techniques for fetal CT ratio with a GA of 17–37 weeks. These nomograms are a simple and reliable screening tool for identifying abnormal fetal heart size.